More sex chromosomes than autosomes in the Amazonian frog Leptodactylus pentadactylus - Gazoni, T. [UNESP]; Haddad, C. F.B. [UNESP]; Narimatsu, H. [UNESP]; Cabral-de-Mello, D. C. [UNESP]; Lyra, M. L. [UNESP]; Parise-Maltempi, P. P. [UNESP] (Springer Nature, 2018)
Heteromorphic sex chromosomes are common in eukaryotes and largely ubiquitous in birds and mammals. The largest number of multiple sex chromosomes in vertebrates known today is found in the monotreme platypus (Ornithorhynchus anatinus, 2n = 52) which exhibits precisely 10 sex chromosomes. Interestingly, fish, amphibians, and reptiles have sex determination mechanisms that do or do not involve morphologically differentiated sex chromosomes. Relatively few amphibian species carry heteromorphic sex chromosomes, and when present, they are frequently represented by only one pair, either XX:XY or ZZ:ZW types. Here, in contrast, with several evidences, from classical and molecular cytogenetic analyses, we found 12 sex chromosomes in a Brazilian population of the smoky jungle frog, designated as Leptodactylus pentadactylus Laurenti, 1768 (Leptodactylinae), which has a karyotype with 2n = 22 chromosomes. Males exhibited an astonishing stable ring-shaped meiotic chain composed of six X and six Y chromosomes. The number of sex chromosomes is larger than the number of autosomes found, and these data represent the largest number of multiple sex chromosomes ever found among vertebrate species. Additionally, sequence and karyotype variation data suggest that this species may represent a complex of species, in which the chromosomal rearrangements may possibly have played an important role in the evolution process.
Keywords: Amphibia; Leptodactylidae; Meiotic multivalents; Multiple sex chromosomes; Translocations